New methods in diagnostic and therapyMagnetic resonance myocardial perfusion imaging – still new or a routinely used tool in coronary artery disease diagnostics? - A. Małek, Łukasz (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2012)
The article presents the newest data on magnetic resonance myocardial perfusion imaging in the diagnostics of coronary artery disease. Studies completed in recent years demonstrate that this method is superior to some other routinely used non-invasive techniques of myocardial ischemia assessment. Non-invasive coronary artery diagnostics consisting of anatomic assessment by means of computed tomography and functional assessment by means of cardiovascular magnetic resonance reduce the frequency of required coronary angiographies and hospitalizations related to them and therefore lowers the risk of invasive diagnostics and costs of treatment.